Coprecipitation and solid-state synthesis of T11212 superconductors and fabrication of dip-coated tapes / Faizah Md. Salleh - Md. Salleh, Faizah (2007)
This thesis describes the synthesis of 111212 superconductor from various starting compositions via coprecipitation and solid-state methods and fabrication of T11212 dip-coated superconductor tapes. Bulk TI 1212 was synthesized from T108Bi02 Sr2Ca08Y02Cu207 nominal starting composition using coprecipitation method with TI-containing (CPI sample) and TI-free (CP3 sample) precursors. The 11-containing precursor route involves calcination of 11-containing precursor powder at 600 °C and sintering of the pellets at various temperatures and durations. The best superconducting sample with 1212 phase of 83 vol.% and Tczero of 94 K was sintered at 870°C for 60 minutes. However, the sample consists of minor T11201 phase and SrCO3 impurity. Addition of nano-MgO particles showed enhanced 1212-phase formation and total elimination of the SrCO 3 impurity. The transport J at 40 K in zero magnetic field for the sample with 0.15 wt.% nano-MgO additions was ten times the J of the sample without MgO and J measurements in external magnetic fields (0- 0.9 1) showed improved magnetic flux pinning property. To reduce Ti loss during sintering of the coprecipitated sample, Ti-free precursor route using two-step synthesis method was developed and was used to synthesize 111212 using the same composition as above. The TI-free precursor was first calcined at 850 °C followed by additions of appropriate amounts of 11203 and Bi203 before sintering at 1000°C for 6 minutes. This resulted in a higher purity sample with T,,,,, of 91 K, J at 40 K of 11.2 A/cm2 and ultrafine grains with average size of 0.5 - 1 m. For comparison purposes, bulk T11212 was also synthesized using Tl 05Pb05 Sr 18Yb02CaCu207 (SS1 sample) and Tl08Bi02 Sr2Ca0, 8Y02Cu207 (SS2 sample) nominal starting compositions using the conventional solid-state method. The results show that both SS1 and SS2 samples have T zero of 94 K and are comparable to the T zero of the coprecipitated samples.